PENGARUH PENAMBAHAN RADIUS PADA KECEPATAN DAN FREKUENSI SLUG DI DAERAH DOWNSTREAM T-JUNCTION MINICHANNEL - Hananto, Leila Hanjani; Indarto; Untung Surya Dharma; Deendarlianto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Multiphase flow channel is commonly applied in various industrial contexts, including lab-on-a-chip, nuclear power plants, microelectronics cooling systems, and chemical microreactors. Equipment ranging from mini to micro sizes plays a vital role in enhancing heat and mass transfer processes during the mixing of two or more phases. Non-uniform phase distribution during the passage of a two-phase flow through a T-junction can cause performance issues in the downstream region. A problem arising from the use of T-junctions is the occurrence of slugs. An experimental study was conducted to investigate the effect of varying bend radius on the flow characteristics in the downstream region of a T-junction minichannel, such as slug velocity and frequency. The slug velocity was researched in the downstream region of the horizontal minichannel T-junction. The working fluid used was air as the gas phase and water. The findings indicate that there is a linear relationship between the superficial velocities of air and water and the corresponding slug velocity in the downstream area of the horizontal minichannel T-junction, as observed through the utilization of a high-speed camera and MATLAB program for image processing. It has been observed that the local velocity within the channel increases as the corner radii increase towards the downstream region.